Analytical modeling and validation of multi-mode piezoelectric energy harvester - Li, Xiangyang (2021)
Energy consumption of electronic devices continues to reduce dramatically, enabling the ambient energy harvesting devices as a solution for powering the wireless sensor nodes (WSNs), micro-electromechanical systems and portable electronics. Over the years, vibration-based piezoelectric harvesting has been emerged as a potential technology to recharge/replace chemical batteries in WSNs. A conventional linear piezoelectric energy harvester (PEH) cannot meet the requirement of broadband vibration resources as it generates useful power only in a narrow bandwidth near the resonant frequency. Several techniques such as passive/active resonance tuning, array of harvester beams, nonlinear designs and multi-degree-of-freedom energy harvesters have been investigated. This paper proposes a generalized multi-mode PEH (MPEH) accompanied with analytical modeling, which generates multiple close peaks of voltage output from low amplitude broadband and low frequency ambient vibration sources. The proposed MPEH comprises of a main cantilevered beam bonded with a patch of piezoelectric layer and attached with multiple branches with tip masses at their free ends. The useful bandwidth and the number of peaks for the MPEH could be tuned conveniently by varying multiple branches and tip masses. The proposed MPEH offers high design flexibility in tuning geometric parameters for achieving target frequencies and generates high power density. The mathematical modeling of generalized MPEH under transverse harmonic base vibrations is presented and the dynamic equations of the multi-modal harvester system are obtained following the Lagrangian method. The derived distributed parametric model of MPEH is more accurate than lumped parametric models of PEHS presented in the literature. The accuracy of the proposed analytical model is validated by two examples with numerical simulation and experimental results. It is shown that the multi-mode PEH has potential to generate sufficient power output from broadband vibration sources to sustain low-power electronic devices.